Tillering Dynamics and Productivity of BRRI dhan44 as Influenced by Spacing and Nitrogen Management Technique - Rashid, Md. Harunur; Khan, Md. Akhter Hossain (Journal of Agriculture & Rural Development, 2008)
The experiment was conducted at the Bangladesh Rice Research Institute farm to study the tillering dynamics and the productivity of the variety, BRRI dhan44 under four spacing (20 cm× 15 cm, 25 cm× 15 cm, 20 cm× 20 cm and 25 cm× 25 cm) and varying levels (0, 60, 80, 100 kg N ha-1) and technique (Leaf Color Chart based N) of N. The wider spacing produced higher number of tillers at maximum tillering stage which was not realized in to number of on ear bearing tiller m-2. Grain yield was not influenced by spacing. A similar grain yield of BRRI dhan44 at a wider spacing of 25 cm× 25 cm indicated its suitability where wider spacing is practiced. The higher amount of added N produced higher non bearing tillers hill-1. Grain yield obtained from 80, 100 kg N ha-1 and leaf color chart (LCCN) was comparable. Key words: Spacing, nitrogen management, tillering dynamics, productivity, rice.